Exaggerated pressor response to static squats in Parkinson's disease (PD) and healthy subjects is likely an individual trait, not influenced by whole body vibration (WBV). - Niewiadomski, Wiktor; Gąsiorowska, Anna; Żyliński, Marek; Karbowniczek, Aleksandra; Cebrat, Justyna; Stępniewska, Anna (NeuroRehabilitation, 2023)
BACKGROUND: Reduced muscle strength is one symptom of Parkinson's disease (PD). Strength can be increased by strength training, which may cause exaggerated blood pressure (BP) rise. It is believed that exercises performed on vibrating platform can strengthen leg muscles without excessive BP increase. OBJECTIVE: To measure the pressor response to static exercises performed during whole body vibration in PD patients. METHODS: Twenty-four aged PD patients and twelve healthy young volunteers participated in the study. PD subjects performed six repetitions of deep-, semi-squat, and calves at vibration frequency of 30 Hz. Each 30 s exercise was followed by 30 s rest. The young volunteers performed two sessions of above-mentioned exercises with and without vibration. BP was measured continuously. RESULTS: In PD patients, the highest BP values were observed during deep squat; systolic blood pressure rose 10 mmHg in 'weak responders', and 50 mmHg in 'strong responders'. This difference correlated with the rise in pulse pressure suggesting indirectly the role of stoke volume in individual response. In healthy subjects pressor response was also individually differentiated and not influenced by vibration. CONCLUSION: Deep and semi squat can evoke a strong cardiovascular response in some PD and healthy subjects. Low-magnitude vibrations likely did not affect pressor response.